The UTAUT Model in the Continuance Intention of E-Wallets (QRIS) by MSMEs: With the Moderating Effect of Security Risk - Tri Yulita Sari; Baihaqi; Irwansyah (Indonesian Journal Economic Review (IJER), 2026)
The post-COVID-19 shift toward a cashless economy in Indonesia has accelerated MSME adoption of digital wallets and QRIS; however, sustaining long-term technology retention remains challenging amid rising cyber threats. Integrating the UTAUT and ECM frameworks, this study examines how performance expectancy, effort expectancy, social influence, and facilitating conditions affect QRIS continuance intention among MSMEs, with perceived security risk as a moderator. This quantitative study collected survey data from 134 active MSME operators in Bengkulu City, Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results reveal that all four UTAUT constructs significantly and positively impact QRIS continuance intention. Crucially, perceived security risk acts as a robust negative moderator, systematically weakening the positive effects of these determinants on long-term retention. Theoretically, this research extends the UTAUT model into a post-adoption business context. Practically, it underscores that sustaining digital payment ecosystems requires a collaborative approach: platform providers must enhance security, regulators must enforce consumer protection, and merchants must elevate digital literacy.